2014
DOI: 10.1136/bjophthalmol-2013-304720
|View full text |Cite
|
Sign up to set email alerts
|

Topical bromfenac reduces the frequency of intravitreal bevacizumab in patients with branch retinal vein occlusion

Abstract: UMIN 14929.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 26 publications
0
9
0
1
Order By: Relevance
“…Also, a lower number of reinjections were observed in the combined treatment [209]. The application of topical bromfenac, a nonsteroidal anti-inflammatory drug during IVB therapy in eyes with ME secondary to BRVO, was found to have the advantage of reducing the number of injections although it did not affect the visual prognosis [210]. Other combination therapies that have been investigated include corticosteroids with laser, anti-VEGF agents with corticosteroids, anti-VEGF agents with laser, and AVS or PPV with corticosteroids, to name a few [211219].…”
Section: Treatmentmentioning
confidence: 99%
“…Also, a lower number of reinjections were observed in the combined treatment [209]. The application of topical bromfenac, a nonsteroidal anti-inflammatory drug during IVB therapy in eyes with ME secondary to BRVO, was found to have the advantage of reducing the number of injections although it did not affect the visual prognosis [210]. Other combination therapies that have been investigated include corticosteroids with laser, anti-VEGF agents with corticosteroids, anti-VEGF agents with laser, and AVS or PPV with corticosteroids, to name a few [211219].…”
Section: Treatmentmentioning
confidence: 99%
“…Several studies have demonstrated that bromfenac decreases eye pain and irritative symptoms following refractive surgery with no signals for increased rates of side effects or adverse changes in VA or healing/corneal epithelialization 6166. Bromfenac has shown promise in reducing retinal thickening in patients with DME and has been reported to be beneficial in the management of uveitic macular edema when used in combination with IVTA or IVB including improvements in CMT and VA69 and reduced frequency of intravitreal injections 70. Results of several studies suggest that topical bromfenac may be beneficial in patients with anterior segment and/or inflammatory ocular surface disorders, including blepharitis,30 conjunctivitis/SAC/vernal keratoconjunctivitis, scleritis/episcleritis,30,7779 dry eye disease,80 anterior uveitis,81 and corneal ulcer pain 23…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of bromfenac 0.1% in combination with IVB in 44 patients (48 eyes) with macular edema related to branch RVO was studied in a prospective case-control pilot study 70. Patients received IVB initially and repeated the treatment when macular edema (defined as foveal thickness ≥300 µm) recurred.…”
Section: Introductionmentioning
confidence: 99%
“…Ponadto w leczeniu skojarzonym zaobserwowano mniejszą liczbę ponownych wstrzyknięć [26,33]. Stwierdzono, że zastosowanie miejscowo bromfenaku, niesteroidowego leku przeciwzapalnego, w oczach z obrzękiem plamki wtórnym do BRVO ma tę zaletę, że zmniejsza liczbę wstrzyknięć, chociaż nie wpływa na ostrość widzenia [26,34]. Inne badane terapie skojarzone to glikokortykosteroidy z laserem, preparaty anty-VEGF z glikokortykosteroidami, preparaty anty--VEGF z laserem i sheatotomia, czyli nacięcie pochewki naczyń (AVS) lub PPV z glikokortykosteroidami [26,[35][36][37][38][39][40][41][42][43].…”
Section: Laseroterapia W Cukrzycowym Obrzęku Plamkiunclassified